1995
DOI: 10.1037/0022-0663.87.3.455
|View full text |Cite
|
Sign up to set email alerts
|

Visual argument: Graphic organizers are superior to outlines in improving learning from text.

Abstract: Most research on graphic organizers (i.e., figural organizations of text information) has failed to simulate actual classroom learning. Typically, studies have used short, poorly organized text, single graphic organizers, and immediate tests measuring only factual knowledge. Also, there is no convincing evidence that graphic organizers are better than outlines. Two experiments were conducted that represented attempts to address these problems in answering the question, "What types of text information do graphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
153
1
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(183 citation statements)
references
References 35 publications
(58 reference statements)
19
153
1
10
Order By: Relevance
“…The approaches in tasks four and ten probably made the users more confident since they found the correct information quickly, which speeded up their performance. This is in line with the studies of visual argument theory carried out by Robinson and Kiewra (1995), since information associated with different regions of a car is best visualized by pictorial maps of a car with hyperlinked zones. Vekiri (2002) summarizes a number of studies by concluding that using appropriate visualization decreases the cognitive load which would result in a more effective processing and learning of information, measured by retention tests and ability to transfer the information to new situations.…”
Section: Efficiency Of the Systems In Terms Of Speed And Incorrect Ansupporting
confidence: 54%
See 1 more Smart Citation
“…The approaches in tasks four and ten probably made the users more confident since they found the correct information quickly, which speeded up their performance. This is in line with the studies of visual argument theory carried out by Robinson and Kiewra (1995), since information associated with different regions of a car is best visualized by pictorial maps of a car with hyperlinked zones. Vekiri (2002) summarizes a number of studies by concluding that using appropriate visualization decreases the cognitive load which would result in a more effective processing and learning of information, measured by retention tests and ability to transfer the information to new situations.…”
Section: Efficiency Of the Systems In Terms Of Speed And Incorrect Ansupporting
confidence: 54%
“…Another cognitive principle is the theory of visual argument, which Robinson and Kiewra (1995) refer to when they suggest the use of diagrams, maps, charts, and graphs. These communicate information through individual elements and arrangement of these elements in space, making it easier for users to perceive and understand relations and patterns than text does.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that the use of visual aids greatly improves information retention and expands students' understanding of unfamiliar concepts (Butcher, 2006;Mayer & Moreno, 1998;Nesbit & Adescope, 2006;Robinson & Kiewra, 1995). Unlike texts, images have immediacy -they can convey a great deal of information quickly and concisely.…”
Section: Visual and Analytical Reasoningmentioning
confidence: 99%
“…One type of prompt encouraged students to organize the information using matrix note-taking, a type of note-taking that emphasizes comparison and contrast and has been found to improve learning over outline format note-taking (Robinson & Kiewra, 1995). Another type of prompt asked students to practice and then apply critical thinking strategies (e.g., looking for bias and examining the quality of evidence that was available to support claims).…”
Section: Prompts For Cognitive Engagementmentioning
confidence: 99%
“…3, and in PytlikZillig, Hutchens, Muhlberger, and Tomkins (2017), prior research has found that students can engage with reading materials in a variety of ways with different effects. For example, people may learn more if they are engaged in deep rather than surface-level processing, and some have found that the manner in which students take notes and organize the information impacts learning (Dinsmore & Alexander, 2012;Robinson & Kiewra, 1995).…”
Section: Prompts For Cognitive Engagementmentioning
confidence: 99%